Genetic variability and heritability studies of some reproductive traits in cowpea (Vigna unguiculata (L.) Walp.) - Omoigui, L.O.; Ishiyaku, M.F.; Kamara, A.Y.; Alabi, S.O.; Mohammed, S.G. (2006)
The success of most crop improvement programs largely depends upon the genetic variability and the heritability of desirable traits. The magnitude and type of genetic variability help the breeder to determine the selection criteria and breeding schemes to be used for improvement purposes. A screen house experiment was carried out at Samaru, Nigeria in 1999 and 2000 dry seasons to estimate the genotypic variability of some reproductive traits and their heritability in some selected cowpea varieties. Results of the study showed that there was considerable variation among cultivars for duration of reproductive phase and rate of photosynthate partitioning. Genotypic coefficients of variation were also high for days to first flower, 100-seed weight, plant height, and harvest index. Broad-sense heritability estimate (h2) was 98.9% for 100-seed weight, 94% for duration of reproductive phase, 84.5% for days to first flower, 83.9% for days to maturity, and 77.3% for harvest index. This information showed that there is sufficient genetic variance to warrant selection for improvement in the cowpea genotypes studied. We concluded that considerable progress in cowpea breeding could be achieved by exploiting these traits.